The American transcendentalists their prose and poetry - Miller, Perry 1905-1963 (Garden City, N.Y. Doubleday, 1957)
Anthology of works by New England writers of the early 1800's
The essential transcendentalist Henry David Thoreau,Journal -- Part I. History and doctrine -- Historic notes of life and letters in New England Ralph Waldo Emerson -- An essay on transcendentalism Charles Mayo Ellis -- A participant's definition William Henry Channing -- A dissenting definition Orestes Augustus Brownson -- Part II. Naturalism -- The method of nature Ralph Waldo Emerson -- Journal Henry David Thoreau -- Orphic sayings Thoreau and Emerson Amos Bronson Alcott -- A transcendental conversation Margaret Fuller -- Part III. Religious radicalism -- A discourse of the transient and permanent in Christianity Theodore Parker -- Part IV. The literary aspiration -- The editors to the reader The Dial -- Walking Henry David Thoreau -- A dialogue Goethe Margaret Fuller -- Beauty Ralph Waldo Emerson -- American literature Margaret Fuller -- Part IV. The poetic endeavor -- Poetry and imagination Poems Ralph Waldo Emerson -- Poems Henry David Thoreau -- Poems William Ellery Channing -- Poems Amos Bronson Alcott -- Poems Margaret Fuller -- Poems Christopher Pearse Cranch -- Questionings Frederick Henry Hedge -- Poems Ellen Sturgis Hooper -- Poems Caroline Sturgis Tappan -- Poems Jones Very -- Part V. Politics and society -- Aristocracy Ralph Waldo Emerson -- Life without principle Henry David Thoreau -- Woman in the nineteenth century Margaret Fuller -- Democracy and liberty Amos Bronson Alcott -- Part VI. Future reference -- The political destination of America and the signs of the times Theodore Parker -- Letter to Mr. Walter Whitman Ralph Waldo Emerson -- Meeting Whitman Henry David Thoreau -- Thoreau Ralph Waldo Emerson
Enchor books edition.
Includes bibliographical references (pages [377]-379) and index.
Keywords: American literature -- New England; American literature -- 19th century; Transcendentalism (New England); New England -- Literary collections